2012
DOI: 10.1007/s00737-012-0301-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subjective birth experiences on post-traumatic stress symptoms: a longitudinal study

Abstract: The aim of this prospective study was to examine the etiology of post-traumatic stress symptoms following childbirth within a transactional framework of stress. Participants were women (N = 1,499) from the Akershus Birth Cohort. These women were followed from pregnancy to 8 weeks postpartum. We modeled predisposing factors (e.g., fear of childbirth) and precipitating factors (subjective and objective birth experiences) as predictors of post-traumatic stress symptoms. Post-traumatic stress symptoms were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
191
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(219 citation statements)
references
References 40 publications
17
191
1
10
Order By: Relevance
“…Even if peritraumatic distress is not included as diagnostic criterion, its relevance as risk factor should be paid attention to (Karam et al, 2010). In the study by Garthus-Niegel et al (2013), comparable results were found, using a similar design in another population. Childbirth as well as spine surgery, among other medical conditions, can serve as research opportunities to study general mechanisms in the development of PTSD.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Even if peritraumatic distress is not included as diagnostic criterion, its relevance as risk factor should be paid attention to (Karam et al, 2010). In the study by Garthus-Niegel et al (2013), comparable results were found, using a similar design in another population. Childbirth as well as spine surgery, among other medical conditions, can serve as research opportunities to study general mechanisms in the development of PTSD.…”
Section: Discussionsupporting
confidence: 65%
“…Peritrauma variables, on the other hand, could influence posttraumatic stress either directly or indirectly through posttrauma variables occurring after the trauma. Childbirth, like elective spine surgery, is a possibly traumatizing event that is highly predictable and therefore a suitable subject for research on the relevance of pre- and peritrauma risk factors in longitudinal studies (Garthus-Niegel, Von Soest, Vollrath, & Eberhard-Gran, 2013; König et al, 2016; van Son, Verkerk, van der Hart, Komproe, & Pop, 2005). While some studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of 1,499 women in Norway examined the role of fear of childbirth, subjective and objective experience of birth in postnatal PTSD symptoms. They found that subjective birth experience had the strongest effect on postpartum PTSD symptoms and mediated the relationships between fear of childbirth, obstetric factors and PTSD (Garthus-Niegel, von Soest, Vollrath, & Eberhard-Gran, 2013).…”
Section: Ptsdmentioning
confidence: 99%
“…A number of authors have emphasized that preventive interventions should be based on the underlying psychological mechanism of traumatic stress symptoms (Ayers et al, 2008;Garthus-Niegel et al, 2013). However, the aetiology of these symptoms remains unclear.…”
Section: Introductionmentioning
confidence: 99%